Plasticity in expression of the glutamate transporters GLT-1 and GLAST in spinal dorsal horn glial cells following partial sciatic nerve ligation - Xin Wen-Jun; Weng Han-Rong; Dougherty Patrick M (SAGE Publishing, 2009)
Abstract Background Clearance of synaptically released glutamate, and hence termination of glutamatergic neurotransmission, is carried out by glutamate transporters, most especially glutamate transporter-1 (GLT-1) and the glutamate-aspartate transporter (GLAST) that are located in astrocytes. It is becoming increasingly well appreciated that changes in the function and expression of GLT-1 and GLAST occur under different physiological and pathological conditions. Here we investigated the plasticity in expression of GLT-1 and GLAST in the spinal dorsal horn using immunohistochemistry following partial sciatic nerve ligation (PSNL) in rats. Results Animals were confirmed to develop hypersensitivity to mechanical stimulation by 7 days following PSNL. Baseline expression of GLT-1 and GLAST in naive animals was only observed in astrocytes and not in either microglia or neurons. Microglia and astrocytes showed evidence of reactivity to the nerve injury when assessed at 7 and 14 days following PSNL evidenced by increased expression of OX-42 and GFAP, respectively. In contrast, the total level of GLT-1 and GLAST protein decreased at both 7 and 14 days after PSNL. Importantly, the cellular location of GLT-1 and GLAST was also altered in response to nerve injury. Whereas activated astrocytes showed a marked decrease in expression of GLT-1 and GLAST, activated microglia showed de novo expression of GLT-1 and GLAST at 7 days after PSNL and this was maintained through day 14. Neurons showed no expression of GLT-1 or GLAST at any time point. Conclusion These results indicate that the expression of glutamate transporters in astrocytes and microglia are differentially regulated following nerve injury.